2020
DOI: 10.1159/000506302
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Late Relapse after Allogeneic Hematopoietic Stem Cell Transplantation in Patients with T-Cell Prolymphocytic Leukemia

Abstract: Initial treatment with the monoclonal anti-CD52 antibody alemtuzumab induces responses in the majority of patients with T-cell prolymphocytic leukemia (T-PLL). In eligible patients, allogeneic hematopoietic stem cell transplantation (allo-HSCT) is an option to consolidate hematological remissions. Here, we report our experience with 10 patients who received allo-HSCT against T-PLL. Notably, 3 patients with complete remission at transplantation and durable full-donor chimerism relapsed at months 12, 59, and 84 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…A PCR-based assessment of minimal residual disease (MRD) kinetics was reported by Sellner et al [12] and confirmed the presence of graft-versus-leukemia effects in T-PLL. In line with the results by Shumilov et al [11], they observed a significant reduction of MRD levels upon immunomodulation in 7/10 patients, but with complete MRD clearance in only 2 patients.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…A PCR-based assessment of minimal residual disease (MRD) kinetics was reported by Sellner et al [12] and confirmed the presence of graft-versus-leukemia effects in T-PLL. In line with the results by Shumilov et al [11], they observed a significant reduction of MRD levels upon immunomodulation in 7/10 patients, but with complete MRD clearance in only 2 patients.…”
supporting
confidence: 90%
“…The authors observed PD (5/10) or NRM (5/10) in all 10 patients and the 2-year OS of 30% and the 4-year OS of 20% was below the OS in the prospective EBMT series [8]. The high NRM in this series [11] was primarily caused by fatal infections, underlining the relevance of infectious complications in the post-transplantation management. CMV reactivations were observed in 6 (60%) patients with a lethal infection in 1 case.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…1 Relapsing disease is usually highly refractory both to conventional chemotherapy and retreatment with alemtuzumab. 1,4,5 Molecular mechanisms underlying resistance to alemtuzumab are largely unknown, but may include down-regulation of its target CD52 on the surface of the leukemic cells. 6,7 However, the molecular reasons for this immunophenotypic change and its clinical significance remain unclear.…”
mentioning
confidence: 99%